2009
DOI: 10.3177/jnsv.55.195
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wasabi Rhizome Extract on Atopic Dermatitis-Like Symptoms in HR-1 Hairless Mice

Abstract: SummaryWe investigated the effect of wasabi rhizome extract on atopic dermatitis (AD) model mice. The wasabi extract was fed to the HR-1 hairless mice, which develop AD-like symptoms with a special diet (HR-AD diet). The extract was expected to reduce the symptoms induced. Wasabi rhizome-containing HR-AD diet (5% and 10%) reduced the scratching behavior, and the 10% wasabi rhizome HR-AD diet significantly reduced scratching behavior on days 28, 35 and 42. Plasma components (histamine, eotaxin, IgE and thymus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…It is known that wasabi inhibits proliferation of bacteria, and this has been studied for many years [1,2]. It has been reported that wasabi rhizome extract and fragrance ingredient had a various biological activities including antiplatelet, anti-atopic dermatitis and anti-tumor effects [3][4][5]. The wasabi leaf extract was used as a cosmetic material, and was also included in the international nomenclature for cosmetic ingredients (INCI) list compiled by the Cosmetics, Toiletries and Fragrances Association [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that wasabi inhibits proliferation of bacteria, and this has been studied for many years [1,2]. It has been reported that wasabi rhizome extract and fragrance ingredient had a various biological activities including antiplatelet, anti-atopic dermatitis and anti-tumor effects [3][4][5]. The wasabi leaf extract was used as a cosmetic material, and was also included in the international nomenclature for cosmetic ingredients (INCI) list compiled by the Cosmetics, Toiletries and Fragrances Association [6].…”
Section: Introductionmentioning
confidence: 99%
“…Grated wasabi rhizome, which contains various isothiocyanates, is a popular condiment in Japan. These isothiocyanates have many physiological functions, including anti-microbial (Isshiki et al, 1992), anti-platelet (Morimitsu et al, 2000), anti-cancer, antioxidative (Morimitsu et al, 2000(Morimitsu et al, , 2002, anti-inflammatory (Uto et al, 2005), anti-diabetic (Fukuchi et al, 2004;Yoshida et al, 2011), and anti-allergic (Nagai and Okunishi, 2009;Yamada-Kato et al, 2012) activities. Furthermore, isothiocyanates are known ligands of transient receptor potential ankyrin 1 (TRPA1) (Jordt et al, 2004;Terada et al, 2015;Uchida et al, 2012).…”
Section: Adrb3 Plays An Important Anti-obesity Role Because Its Agonistsmentioning
confidence: 99%
“…6-MSITC has been studied for its physiological functions, including antioxidative (Hou et al, 2011, Morimitsu et al, 2002, Yamada-Kato et al, 2017, neuroprotective (Trio et al, 2016), antiplatelet (Morimitsu et al, 2000), anticancer (Morimitsu et al, 2000;Watanabe et al, 2003), detoxifying (Morimitsu et al, 2000;Toyama et al, 2011), antiinflammatory (Uto et al, 2005), antidiabetic (Fukuchi et al, 2004;Yoshida et al, 2011), and antiallergenic properties (Nagai and Okunishi, 2009;Yamada-Kato et al, 2012). However, the stimulatory effects of 6-MSITC and other ITCs on hair growth have not been reported.…”
Section: Introductionmentioning
confidence: 99%